Designer Selves in Tom Wolfe's The Bonfire of the Vanities and Danielle Steel's Crossings - Hildegard Hoeller (Names, 1994)
Abstract Both Tom Wolfe in his realist novel The Bonfire of the Vanities and Danielle Steel in her sentimental novel Crossings use designer and brand names as narrative tools. While such a use of designer names enhances the verisimilitude of the novels, it also involves both authors in complex, post-modern revisions of the nineteenth century literary traditions - realism and sentimental fiction - they place themselves in.